OUTBURST DECLINE OF SLOW NOVA RT SERPENTIS (1909) FROM 1940 TO 1993. - Bochkov, V. V.; Pavlenko, E. P.; Vasiljanovskaja, O. P. (Одеські астрономічні публікації, 2017)
We present observations of the Nova RT Ser (1909) from 1940 to 1978 (pbotograhic magnitudes) and from 1983 to 1993 (B, V, R). Light variations with typical time of 10 years have been detected. Brightness declines at a rate of 0.06 magnitude per year during last 70 years.